A Clinical Case of Effective Treatment of Pneumonia Caused by Polyresistant Strains with the Use of Inhalation Colistimethate Sodium - M. A. Balalaeva; L. V. Selivanova; O. V. Dymova; D. V. Bazarov; E. V. Chernova; M. V. Lukina; A. A. Eremenko (Вестник анестезиологии и реаниматологии)
Patients with nosocomial infections stay in the hospital 2–3 times longer than patients without signs of infection.It results in 3–4-fold increase of costs and 5–7-fold elevated risk of death. The choice of rational regimes of antimicrobial therapy in such cases is very difficult.The objective: to demonstrate the efficacy of a combination of prolonged intravenous infusion of meropenem and inhaled sodium colistimethate in the treatment of the patient with the pulmonary infection caused by Kl. pneumoniae and Ac. baumanii, which were resistant to a wide range of antibiotics.